1973
DOI: 10.1139/m73-054
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and cell division of an oral bacterium resembling Alysiella filiformis

Abstract: Alysiella filiformis is commonly found on the epithelial cells of the oral cavity in rabbits. An ultra-structural study of these cells has shown A. filiformis attached by numerous slime appendages (setae) to the host epithelial cells. The organism possesses a multilayered cell wall 18–22 nm thick. Cell division occurs by constriction of the cytoplasm with concurrent septum formation initiating from the dense innermost layer of the cell wall. This is followed by thickening and delamination of the septum with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Besides multicellularity, another peculiarity of Alysiella , Simonsiella and Conchiformibius is that they divide longitudinally ( 11 , 18 , 19 and this manuscript). This is extraordinary, given that, except for nematode 20 , 21 , insect 22 and dolphin symbionts 23 , rod-shaped bacteria typically elongate and divide by transverse fission, two processes coordinated by the elongasome and divisome, respectively.…”
Section: Introductionmentioning
confidence: 76%
“…Besides multicellularity, another peculiarity of Alysiella , Simonsiella and Conchiformibius is that they divide longitudinally ( 11 , 18 , 19 and this manuscript). This is extraordinary, given that, except for nematode 20 , 21 , insect 22 and dolphin symbionts 23 , rod-shaped bacteria typically elongate and divide by transverse fission, two processes coordinated by the elongasome and divisome, respectively.…”
Section: Introductionmentioning
confidence: 76%
“…Table 3 shows that the capability of the cells to adsorb the K-specific phage 29 became measurable around 15 min after shift down. Adsorbed phage 29 particles were demonstrable (in ultrathin sections) about 20 min after temperature shift down (M. E. Bayer and H. Thurow, manuscript in preparation). Two hours after shift down were required to reveal in the light microscope (using India ink stain) the first signs of an ill-defined halo around the mutant cells.…”
Section: T\'mentioning
confidence: 99%
“…The bacterial capsule is involved in a variety of functions, such as cementing freshwater bacteria together (7) to form large films (28) or facilitating adhesion of marine bacteria to solid surfaces (18); furthermore, capsulated cells seem to be protected from adverse environmental conditions (12). Capsulated cells are also found in the oral flora (29), with polysaccharides serving as aggregation substances (32) and possibly playing a role in dental plaque and caries (20). Of special significance to our work is that the capsule hinders the attack by bacteriophages specific for 0-antigens and lipopoly-saccharides; it also protects the cells from phagocytosis by macrophages (39).…”
mentioning
confidence: 99%
“…Bae et al (1) have examined bacterial cells directly from soil and have found that most of these cells are surrounded by thick capsules, and Fletcher and Floodgate (17) and Jones et al (26) have shown that many aquatic bacteria are surrounded by an acidic polysaccharide capsule, which mediates their adhesion to solid surfaces. Kaiser and Starzyk (27) have shown that cells of Alysiella adhere to the oral epithelium by means of a capsular structure. Shands has shown (40) that pathogenic cells of Salmonella typhimurium are surrounded by a very thick capsule within the tissue of an infected mouse, and these current observations indicate that most bovine rumen bacteria have both additional surface layers and extensive capsules.…”
Section: -M _mentioning
confidence: 99%
“…Because of their phenomenally thick peptidoglycan layer, cells of M. elsdenii are excellent material for the examination of the process of septum formation, and thick septa can be clearly seen in all stages of cell division. In this respect those cells resemble the trichome-forming Simonsiella (31) and Alysiella (27), and M. elsdenii also resembles these organisms in that the elastic (15) outer layers of the cell wall take no significant part in the centripetal growth of the septum. Freeze-etching has shown this developing septum directly, and its location is reflected by a "furrowing" at the cell surface in M. elsdenii.…”
mentioning
confidence: 94%